Linguagem e representação nos autos de um processo penal: como operadores do direito representam atores sociais em um sistema de gêneros - Fuzer, Cristiane (2008)
This work tries to answer the following question: how law operators represent social actors in the penal process in a crime against life in the Brazilian context? The main objective consists of analyzing the forms of representation of social actors, based on the description of the transitivity system, in texts produced by the operators in a penal process. To do that, it was necessary to gather contextual data about the legal practice. Through the research on a documental source, constituted by laws and informative texts in the Legal Law area, we have identified mechanisms of institutionalization and we have built the context of culture. We have also built the context of situation in which a particular penal process (PP) is inserted, selected in the 1st Vara Criminal of the Santa Maria Forum, RS, Brazil. Through a qualitative method, we have identified the social actors who fill in the roles of transitivity on the clause level, based on the Systemic Functional Grammar developed by Halliday & Matthiessen (1999, 2004), and we have analyzed the forms of representation, based on the socio-semantic categories proposed by van Leeuwen (1997). The analysis of lexical-grammatical choices associated with contextual data showed the penal process documents constitute a complex system of genres in which the law operators administrate , according to their activities and purposes, the representations of reality construed by the defendant and witnesses. This way, the Law operators use the language to elaborate versions of reality one of which is chosen by the jury.